Phyllonema aviceniicola gen. nov., sp nov and Foliisarcina bertiogensis gen. nov., sp nov., epiphyllic cyanobacteria associated with Avicennia schaueriana leaves - Alvarenga, Danillo Oliveira; Rigonato, Janaina; Branco, Luis Henrique Zanini [UNESP]; Melo, Itamar Soares; Fiore, Marli Fatima (Microbiology Soc, 2016)
Cyanobacteria dwelling on the salt-excreting leaves of the mangrove tree Avicennia schaueriana were isolated and characterized by ecological, morphological and genetic approaches. Leaves were collected in a mangrove with a history of oil contamination on the coastline of Sao Paulo state, Brazil, and isolation was achieved by smearing leaves on the surface of solid media or by submerging leaves in liquid media. Twenty-nine isolated strains were shown to belong to five cyanobacterial orders (thirteen to Synechococcales, seven to Nostocales, seven to Pleurocapsales, one to Chroococcales, and one to Oscillatoriales) according to morphological and 16S rRNA gene sequence evaluations. More detailed investigations pointed six Rivulariacean and four Xenococcacean strains as novel taxa. These strains were classified as Phyllonema gen. nov. (type species Phyllonema aviceniicola sp. nov. with type strain CENA341(T)) and Foliisarcina gen. nov. (type species Foliisarcina bertiogensis sp. nov. with type strain CENA333(T)), according to the International Code of Nomenclature for Algae, Fungi, and Plants. This investigation shows some of the unique cyanobacteria inhabiting the phyllosphere of Avicennia schaueriana can be retrieved by culturing techniques, improving current taxonomy and providing new insights into the evolution, ecology, and biogeography of this phylum.